Field efficacy and safety of Felpreva® (tigolaner, emodepside and praziquantel) spot-on for the treatment of natural ear mite infestations (Otodectes cynotis) and notoedric mange (Notoedres cati) in cats - Katrin Blazejak; Dejan Cvejić; Klaus Hellmann; Hannah Ringeisen; Hannah Hamburg; Gabriele Petry; Tanja N. Knoppe; Norbert Mencke (Current Research in Parasitology and Vector-Borne Diseases, 2023)
The miticide efficacy of a single treatment with Felpreva® (tigolaner, emodepside and praziquantel) spot-on solution for cats was evaluated in two European field studies. One study was conducted in cats naturally infested with Otodectes cynotis. The other study was conducted in cats naturally infested with Notoedres cati. In both studies, the presence of viable mites was confirmed prior to treatment (Day -1/Day 0) and re-evaluated on Day 14 (O. cynotis study) and on Day 28 (both studies). Efficacy was calculated based on the number of viable mites found after treatment. In the O. cynotis study, the primary criterion was the percentage of mite-free cats after treatment with Felpreva® compared to a sarolaner/selamectin combination (Stronghold® Plus, Zoetis) as a positive control. In the N. cati study, the primary criterion was the difference between arithmetic mean mite counts of cats treated with Felpreva® and cats treated with a placebo formulation (solketal). Secondary criteria in both studies were changes in clinical lesion scores after treatment. In both studies, all Felpreva®-treated cats were mite-free (100% parasitological cure) on Day 28, 4 weeks after treatment. Signs of mange on Day 28 were clinically improved in all O. cynotis-infested cats (100%) and clinically cured in all N. cati-infested cats (100%). There were no records of any adverse events or application site reactions in Felpreva®-treated cats.